Comparison of retrograde intrarenal surgery versus a single-session percutaneous nephrolithotomy for lower-pole stones with a diameter of 15 to 30 mm: A propensity score-matching study - Jung, Gyoo Hwan (Korean J Urol, 2015)
PURPOSE: To investigate surgical outcomes between retrograde intrarenal surgery (RIRS) and percutaneous nephrolithotomy (PNL) groups for a main stone sized 15 to 30 mm and located in the lower-pole calyx. MATERIALS AND METHODS: Patients who underwent PNL or RIRS for a main stone sized 15 to 30 mm and located in the lower-pole calyx were retrospectively reviewed. Each patient in the RIRS group was matched to one in the PNL group on the basis of calculated propensity scores by use of age, sex, body mass index, previous treatment history, stone site, maximum stone size, and stone volume. We compared perioperative outcomes between the unmatched and matched groups. RESULTS: Patients underwent PNL (n=87, 66.4%) or RIRS (n=44, 33.6%). After matching, 44 patients in each group were included. Mean patient age was 54.4±13.7 years. Perioperative hemoglobin drop was significantly higher and the hospital stay was longer in the PNL group than in the RIRS group. The operative time was significantly longer in the RIRS group than in the PNL group. Stone-free rates were higher and complications rates were lower in the RIRS group than in the PNL group without statistical significance. The presence of a stone located in the lower-anterior minor calyx was a predictor of stone-free status. CONCLUSIONS: RIRS and single-session PNL for patients with a main stone of 15 to 30 mm located in the lower-pole calyx showed comparable surgical results. However, RIRS can be performed more safely than PNL with less bleeding. Stones in the lower-anterior minor calyx should be carefully removed during these procedures.